1990
DOI: 10.1136/bmj.301.6742.22
|View full text |Cite
|
Sign up to set email alerts
|

A study of patients attending without appointments in an urban general practice.

Abstract: Objective-To ascertain which social and psychological characteristics are associated with patients attending surgeries without appointments.Design-Prospective study of patients attending an urban centre group practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Previous research suggests that younger people, 11 and patients in deprived areas, 12,13 are more likely to use same-day appointments, which is in line with the present findings. The relationship between the present findings and some other studies is less clear.…”
Section: Comparison With Existing Literaturesupporting
confidence: 82%
“…Previous research suggests that younger people, 11 and patients in deprived areas, 12,13 are more likely to use same-day appointments, which is in line with the present findings. The relationship between the present findings and some other studies is less clear.…”
Section: Comparison With Existing Literaturesupporting
confidence: 82%
“…Most of these systems have been studied in reference to the various branches of medicine, but there is a paucity of literature related to pediatric dentistry. Most of these systems have concluded that though appointment scheduling does help to improve the quality of health care delivery, not all the systems may be patient friendly and patient satisfaction with these systems varies [ 12 , 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…), it is not entirely possible to eliminate no-shows (Barron 1980). On the other hand, strong links are found between a tendency to attend without an appointment and lower social class and perception of urgency by Taylor (1984) and Virji (1990). These findings suggest that a clinic that denies access to walk-ins may further disadvantage these groups.…”
Section: Adjustments For No-shows Walk-ins Urgent Patients Emergencie...mentioning
confidence: 92%